2007
DOI: 10.1111/j.1600-0501.2007.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous progression of ligature induced peri‐implantitis at implants with different surface roughness: an experimental study in dogs

Abstract: It is suggested that the progression of peri-implantitis, if left untreated, is more pronounced at implants with a moderately rough surface than at implants with a polished surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
170
2
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(188 citation statements)
references
References 14 publications
7
170
2
9
Order By: Relevance
“…Berglundh et al 20 investigated SBAES in spontaneous progression of peri-implantitis in dogs and concluded that progression of peri-implantitis is more pronounced on rough surfaces than on smooth ones. In this context, Pongnarisorn et al 21 assessed the effects of different surface treatments on the transmucosal area of implants (machined, acid-etched, and anodized) and suggested that the development of implant-associated inflammation is not dependent upon the type of surface or roughness, but rather upon the presence of bacterial plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Berglundh et al 20 investigated SBAES in spontaneous progression of peri-implantitis in dogs and concluded that progression of peri-implantitis is more pronounced on rough surfaces than on smooth ones. In this context, Pongnarisorn et al 21 assessed the effects of different surface treatments on the transmucosal area of implants (machined, acid-etched, and anodized) and suggested that the development of implant-associated inflammation is not dependent upon the type of surface or roughness, but rather upon the presence of bacterial plaque.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear if the microbial composition of a biofilm is affected by the physicochemical properties and texture characteristics of the implant surface. Higher roughness and higher free energy of the implant surface may favour biofilm formation (35), whereas peri-implantitis may occur earlier, with a faster and more extensive progression in implants with rougher surface (36)(37)(38). Nevertheless, it is also shown that abutments with different surface characteristics can influence neither biofilm formation on the implant surface, nor the extent and cellular composition of the resulting inflammatory lesion (39).…”
Section: Such As Staphylococcus Aureus Staphylococcus Epidermidis Ementioning
confidence: 99%
“…The presence of microorganisms in the periimplant tissues may lead to a chronic inflammatory response causing implant failure. Periimplantitis can lead to implant loss in later stages (6,8,9) and a correlation between biofilm accumulation and progressive periimplant bone loss has been reported in experimental and clinical studies (6,7,10).…”
Section: Introductionmentioning
confidence: 99%